Unique selectivity trends of highly permeable PAP[5] water channel membranes. (12th July 2018) - Song, Woochul; Shen, Yue-xiao; Lang, Chao; Saha, Prantik; Zenyuk, Iryna V.; Hickey, Robert J.; Kumar, Manish
Abstract : In this paper, two unique selectivity trends of ML-PAP[5] membranes are discussed from the perspectives of channel geometry, ion exclusion, and linear molecule transport. Abstract : Artificial water channels are a practical alternative to biological water channels for achieving exceptional water permeability and selectivity in a stable and scalable architecture. However, channel-based membrane fabrication faces critical barriers such as: (1) increasing pore density to achieve measurable gains in permeability while maintaining selectivity, and (2) scale-up to practical membrane sizes for applications. Recently, we proposed a technique to prepare channel-based membranes using peptide-appended pillar[5]arene (PAP[5]) artificial water channels, addressing the above challenges. These multi-layered PAP[5] membranes (ML-PAP[5]) showed significantly improved water permeability compared to commercial membranes with similar molecular weight cut-offs. However, due to the distinctive pore structure of water channels and the layer-by-layer architecture of the membrane, the separation behavior is unique and was still not fully understood. In this paper, two unique selectivity trends of ML-PAP[5] membranes are discussed from the perspectives of channel geometry, ion exclusion, and linear molecule transport.